2020
DOI: 10.3390/app11010044
|View full text |Cite
|
Sign up to set email alerts
|

Alien Wood Species as a Resource for Wood-Plastic Composites

Abstract: Since invasive alien species are one of the main causes of biodiversity loss in the region and thus of changes in ecosystem services, it is important to find the best possible solution for their removal from nature and the best practice for their usability. The aim of the study was to investigate their properties as components of wood-plastic composites and to investigate the properties of the wood-plastic composites produced. The overall objective was to test the potential of available alien plant species as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…21 Several studies have shown that the physical and mechanical properties of a composite panel have greatly improved when there is more interaction occurred between the binder and the fiber particles. 22 In addition, research has demonstrated that a sufficient amount and a homogeneous combination of binder with fiber particles are capable of filling the fiber particle bonding gap or void structure in composite panel cavities, hence enhancing their physical and mechanical properties. 23 The advantages and disadvantages of binder were listed in Table 1.…”
Section: Composite Panelmentioning
confidence: 99%
“…21 Several studies have shown that the physical and mechanical properties of a composite panel have greatly improved when there is more interaction occurred between the binder and the fiber particles. 22 In addition, research has demonstrated that a sufficient amount and a homogeneous combination of binder with fiber particles are capable of filling the fiber particle bonding gap or void structure in composite panel cavities, hence enhancing their physical and mechanical properties. 23 The advantages and disadvantages of binder were listed in Table 1.…”
Section: Composite Panelmentioning
confidence: 99%
“…Table 1 shows several invasive plants with animicrobial properties and some species of microorganisms whose development is inhibited by them. Improving the quality of materials Medved et al (2020) have successfully used the woody debris of five invasive species (Table 1) to make wood-plastic composites. Zhao et al (2021) utilised the biomass of Phalaris arundinacea and Lonicera japonica to reinforce the PHBV thermoplastic.…”
Section: Biopesticide Productionmentioning
confidence: 99%
“…The article deals with two starting materials: (i) wood, which is expected to have high price volatility and therefore should be considered by producers for alternative uses and (ii) straw, for which it is necessary to find a compromise between its use and its incorporation into the soil (burning, ploughing and similar) to maintain nutrients in the system [16][17][18][19]. It is noteworthy to mention that recycled wood and post-harvest residues could replace conventional raw materials in the forthcoming future, as there is clear evidence that in the future there will be a lack of wood materials, especially in the woodworking, energy and other sectors [20][21][22]. In addition, it is worth mentioning post-consumer wood waste, e.g., post-consumer wood fibreboard waste [23].…”
Section: Introductionmentioning
confidence: 99%